Entre a escola e o trabalho: uma análise ergológico discursiva do estágio no Ensino Médio Técnico - Fonseca, Fábio Carlos de Mattos da (2017)
The general objective of this research is to investigate the supervised traineeship in Technical Secondary Education as a training process which integrates heterogeneous meanings and forms of knowledge by mobilising the involved protagonists, specifically the trainee, the adviser and the supervisor. To choose the supervised traineeship as the central research theme is due to its own specificity: its ambiguous, hybrid nature, the fact that it is exactly located at the intersection of two worlds: that of training and that of profession. The study inscribes itself into a theoretical multi-disciplinary perspective which involves Ergology (Schwartz, 2002; Schwartz & Durrive, 2007; Schwartz, 2011) and the Discourse Analysis based upon the theory of enunciation (Maingueneau, 1997; 2008). The methodological proposal realises a crossing of some procedures: (a) documentary research of prescriptions/norms; (b) observation in loco of the traineeship activities; (c) exploration and analysis of verbalisations about the supervised traineeship, by means of interviews, of self-confrontation sessions and of an Encounter group about the traineeship organised in partnership with a research collective that was formed especially for this work. The analysis process of the verbalisations focused on the notions and categories which derive as well from the ergologic approach as from the enunciative and discursive perspective of language studies: respectively activity, values, norms and knowledge on the one side and, on the other, planes of enunciation, over-assertion, polemical negation, discursive modalities, argumentative operators and reported speech. The results point to the necessity of a better articulation between the institutions that are directly involved in the traineeship, namely that of education and that which receives trainees in its functional frameworks, even if one recognises a certain infidelity between them, which means that one is not reducible to the other; of valorisation of the knowledge of experience, that is to say, the knowledge invested in the activity, as a form of exceeding the limits the academic knowledge is confronted with in the course of the formative process. A possible way of exceeding this framework is exactly the permanent construction of devices which are able to give a voice to those who are directly involved and who have a relationship with knowledge and with their peers according to a world of values which is transversal to them